The Time Course of Inhibition of Return: Evidence from Steady-State Visual Evoked Potentials - Li, Ai-Su; Zhang, Gong-Liang; Miao, Cheng-Guo; Wang, Shuang; Zhang, Ming; Zhang, Yang (Frontiers in Psychology, 2017)
Inhibition of return (IOR) refers to slower responses to targets at a previously cued location than that at an uncued location. The time course of IOR has long been a topic of interest in the field. Investigations into the time course of IOR are typically performed by examining the magnitude of IOR under various cue-target onset asynchrony (CTOA) conditions. Therefore, the results are vulnerable to influence of factors that could affect the target processes (e.g., the frequency of the target type). In the present study, steady-state visual evoked potentials (SSVEPs) were implemented to directly take a continuous measurement of the degree to which cued location is processed, eliminating the influence mentioned above. The results indicate that, relative to the baseline interval (-400 – 0 ms), the presence of peripheral cues generated a typical two-stage effect on the SSVEP amplitude evoked by a 20 Hz flicker. Specifically, after the onset of the peripheral cues, the SSVEP amplitude first showed a significant increase, which subsequently turned into a significant inhibition effect after 200 ms. These results provide a continuous time course diagram of the cueing effect and suggest an effective way for future investigations of controlling the masking effects of target stimuli processing on IOR.